Don Quixote or the First Modern Subject (Cultura Económica, 2018)
This work intends to analyze the figure of Don Quixote, in the novel of Cervantes, in the light of a general theory of the three narrative matrixes (cosmogonic, heroic, and novelistic) that define the gradual decline in will, power and effectiveness of the actant-subject in its relations with the world-object. The case of Don Quixote presents itself as emblematic of the new modern subjectivity, not only because it inaugurates the model of a subject of omnipotent pretensions vis-a-vis objective reality, but because it anticipates, and in a certain way consumes, the entire parable of Modernity, by presenting the evolution of that initial omnipotent and effective subject towards ineffectiveness, impotence, apathy and failure.
Keywords: Don Quixote; subject; object; Modernity; narrative matrix; heroism; antiheroism